2010
DOI: 10.3113/fai.2010.0592
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term Results of the MOJE Hallux MP Joint Replacement

Abstract: In spite of the good clinical outcome at the mid-term stage with 91% implant survival, given the widespread loosening and subsidence encountered in our study, the long-term outcome following this procedure is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…2,12,17,27,29 Nevertheless, some studies with shorter follow-up showed similar mean AOFAS scores as the present study (Table 2). 6,23 Although some studies with short-term follow-up have shown a low frequency of revision, 11,15,17 studies with longer follow-up have shown higher frequency of revision, consistent with the present results (Table 2). 23,26 Therefore, longer follow-up is needed to evaluate the long-term implant survival of first MP joint replacement.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…2,12,17,27,29 Nevertheless, some studies with shorter follow-up showed similar mean AOFAS scores as the present study (Table 2). 6,23 Although some studies with short-term follow-up have shown a low frequency of revision, 11,15,17 studies with longer follow-up have shown higher frequency of revision, consistent with the present results (Table 2). 23,26 Therefore, longer follow-up is needed to evaluate the long-term implant survival of first MP joint replacement.…”
Section: Discussionsupporting
confidence: 91%
“…6,23 Although some studies with short-term follow-up have shown a low frequency of revision, 11,15,17 studies with longer follow-up have shown higher frequency of revision, consistent with the present results (Table 2). 23,26 Therefore, longer follow-up is needed to evaluate the long-term implant survival of first MP joint replacement. Data reported as number (patients, feet, follow-up in months, number of revisions), percentage (%) of revised feet, or mean ± SD (range, minimum to maximum).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Also, 30 of the initial 42 implants were X rayed at 24 months, and 4 of the 30 showed evidence of progressive loosening. A larger study was published by McGraw et al 38 that included 63 component systems in 48 patients, with a mean follow-up of 44 months. Even though the postoperative AOFAS score was 72, they questioned whether use of this implant should be continued.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] A randomized controlled trial of 39 metal alloy MTP joint replacements showed subsidence of the phalangeal component requiring revision in 6 toes and radiographic loosening in a further 8 toes for a loosening rate of 35% at 2 years. [11][12][13] A randomized controlled trial of 39 metal alloy MTP joint replacements showed subsidence of the phalangeal component requiring revision in 6 toes and radiographic loosening in a further 8 toes for a loosening rate of 35% at 2 years.…”
Section: Historical Perspectivementioning
confidence: 99%